HAMBATAN PENYERAPAN KREDIT USAHA KECIL STUDI KASUS DI PASAR ANYAR I SINGARAJA BALI - Maryatmo, R; Rahayu, Nyoman Yuyun Sri (Semarang State University, 2009)
There were anomaly financial condition in Indonesia. Before 2008 net export were positif in one side,but there were strong financial inflow on another side. The flux of financial supply were not followed bythe financial absorbtion of the real sector. The study is going to investigate the problems of the realsector in absorbing the oversupply of capital market. Especially the study is dedicated to investigate theproblems of small peddler in Pasar Anyar I, Singaraja, Bali in absorbing the credit of banks. It is foundout that inelastic service of banking sectors in determining the time limit, amount of credit, and thebanking requirement for collateral are unaccepted for small peddlers. Small peddler with small capital buthigh return, and high capital circulation, which are vulnerable for economic shock, need fast service,without collateral, and elastic time limit, of credits. The mismatch of service and demand for fund forformal banking creates informal banking to be survived even they charge a higher interest.Keyword: Credit, Small peddler and Small capital